2015
DOI: 10.1371/journal.pone.0130403
|View full text |Cite|
|
Sign up to set email alerts
|

Recollection-Based Retrieval Is Influenced by Contextual Variation at Encoding but Not at Retrieval

Abstract: In this article, we investigated the effects of variations at encoding and retrieval on recollection. We argue that recollection is more likely to be affected by the processing that information undergoes at encoding than at retrieval. To date, manipulations shown to affect recollection were typically carried out at encoding. Therefore, an open question is whether these same manipulations would also affect recollection when carried out at retrieval, or whether there is an inherent connection between their effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 84 publications
1
9
0
Order By: Relevance
“…First, the role of time course in context-dependent memory retrieval was evaluated by analyzing the vincentized cumulative RT distribution (Ratcliff, 1979) in the present study, rather than manipulating the time course. In a future study, the impact of time course can be further investigated by experimentally manipulating the response deadline (see Rosenstreich and Goshen-Gottstein, 2015, for a detailed discussion) and examining the contextual similarity effect in the fast vs. slow conditions. Second, recent studies suggest that attention may select the stimuli in a periodic manner (e.g., VanRullen et al, 2007;Landau and Fries, 2012), such as switching between the cue and target in a rhythmic manner (e.g., Chen et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…First, the role of time course in context-dependent memory retrieval was evaluated by analyzing the vincentized cumulative RT distribution (Ratcliff, 1979) in the present study, rather than manipulating the time course. In a future study, the impact of time course can be further investigated by experimentally manipulating the response deadline (see Rosenstreich and Goshen-Gottstein, 2015, for a detailed discussion) and examining the contextual similarity effect in the fast vs. slow conditions. Second, recent studies suggest that attention may select the stimuli in a periodic manner (e.g., VanRullen et al, 2007;Landau and Fries, 2012), such as switching between the cue and target in a rhythmic manner (e.g., Chen et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Recollection is not always successful because it requires intentional and conscious processing of limited information-cognitive resources. In line with this claim, several studies found that recollection is strongly related both to attentional resources (e.g., Knott & Dewhurst, 2007;Rosenstreich & Goshen-Gottstein, 2015) and to working memory capacity (WMC; e.g., Elward, Evans, & Wilding, 2013). It seems reasonable to expect that factors enhancing the availability of attentional resources and WMC will also improve retrieving information from episodic memory.…”
Section: Mindfulness and Episodic Memorymentioning
confidence: 89%
“…The topic of conscious or controlled processes and unconscious or automatic process of memory has been widely debated in the literature over the past decades (Butler & Berry, 2001;Gruppuso, Lindsay, & Kelley, 1997;Jacoby, 1991;Koen & Yonelinas, 2016;Roediger, 1990;Rosenstreich & Goshen-Gottstein, 2015;Timmermans & Cleeremans, 2015;Toth & Parks, 2006;Yonelinas, 2002). Implicit and explicit memory corresponds to the level of consciousness LEARNING IN A VIRTUAL ENVIRONMENT 9 or awareness shown by a subject in recall and recognition tasks.…”
Section: Applying a Process Dissociation Procedures In Virtual Realitymentioning
confidence: 99%